1999
DOI: 10.1083/jcb.144.5.947
|View full text |Cite
|
Sign up to set email alerts
|

Control of Mitotic Spindle Position by the Saccharomyces cerevisiae Formin Bni1p

Abstract: Alignment of the mitotic spindle with the axis of cell division is an essential process in Saccharomyces cerevisiae that is mediated by interactions between cytoplasmic microtubules and the cell cortex. We found that a cortical protein, the yeast formin Bni1p, was required for spindle orientation. Two striking abnormalities were observed in bni1Δ cells. First, the initial movement of the spindle pole body (SPB) toward the emerging bud was defective. This phenotype is similar to that previously observed in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
142
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 72 publications
15
142
1
Order By: Relevance
“…During mitosis, spindle positioning involves a cortical-microtubule capture mechanism and several proteins are involved in the interaction between microtubules and the cortex [26,27]. In Saccharomyces cerevisiae, microtubule cortical attachment includes mediation by actin, Kar9p, Bud6p and Bni1p [28,29]. Verlhac et al [14] found that actin distribution was disturbed in mos -/-oocytes, which lends strong support to our data.…”
Section: Discussionsupporting
confidence: 87%
“…During mitosis, spindle positioning involves a cortical-microtubule capture mechanism and several proteins are involved in the interaction between microtubules and the cortex [26,27]. In Saccharomyces cerevisiae, microtubule cortical attachment includes mediation by actin, Kar9p, Bud6p and Bni1p [28,29]. Verlhac et al [14] found that actin distribution was disturbed in mos -/-oocytes, which lends strong support to our data.…”
Section: Discussionsupporting
confidence: 87%
“…Both formins promote actin cable assembly Sagot et al, 2002a), but the loss of Bnr1p causes only a mild delay in cell separation (Vallen et al, 2000), whereas the absence of Bni1p causes a widened bud neck (Jansen et al, 1996;Zahner et al, 1996;Mosch and Fink, 1997;Sheu et al, 2000), an inability to engage in tip-directed growth (Evangelista et al, 1997;Mosch and Fink, 1997;Sheu et al, 2000;Ozaki-Kuroda et al, 2001), a defect in bipolar bud site selection (Zahner et al, 1996), a partial defect in cytokinetic ring contraction (Vallen et al, 2000), a defect in early spindle alignment Lee et al, 1999), and a variety of synthetic lethal genetic interactions (Kohno et al, 1996;Longtine et al, 1996;Fujiwara et al, 1998;Fujiwara et al, 1999;Lee et al, 1999;Tong et al, 2001Tong et al, , 2004. We suggest that many, if not all, of these can be attributed to the actin assembly activity of the two formins in conjunction with their specific localizations.…”
Section: Discussionmentioning
confidence: 99%
“…This provides an explanation for the inability of bni1⌬ yeast to undergo tip-directed growth (Evangelista et al, 1997;Mosch and Fink, 1997;Sheu et al, 2000;OzakiKuroda et al, 2001) or to bud in a bipolar manner (Zahner et al, 1996), which in turn requires tip-directed growth (Sheu et al, 2000). Other myosin-V-dependent cargoes also lose their tip-association in bni1⌬ cells, including the microtubule anchoring protein Kar9p (Miller et al, 1999), cytoplasmic microtubules (Segal et al, 2000), and the ASH1 mRNA (Takizawa et al, 1997;Beach et al, 1999), explaining the inability of bni1⌬ yeast to orient the mitotic spindle early in the cell cycle Lee et al, 1999) or to properly restrict Ash1p-mediated cell differentiation to daughter cells (Jansen et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Ase1p contributes to nuclear positioning is further supported by the observation that ase1D leads to a lethal phenotype when combined with mutations in many genes that code for proteins that are involved in nuclear migration, including Arp1p, Bik1p, Bni1p, Bim1p, Kip2p, Dyn1p, Dyn2p, Num1p, Jnm1p, Pac1p and Pac11p. 21,36,37 Future works will determine the exact molecular mechanism by which Ase1p and Cin8p affect the balance of force that act on the nucleus during nuclear migration.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%